Enhancement of ÏâÏ aromatic interactions between hydrophobic Ionic Liquids and Methylene Blue for an optimum removal efficiency and assessment of toxicity by microbiological method - Kermanioryani, M. (Elsevier Ltd, 2016)
Due to their harmful effects on human's life and aquatic environments, designing easy and swift yet efficient methodologies to remove pollutants from water stream is one of the important tasks of the scientific community. Among the pollutants, dyes have a significant role on water pollution, because their presence, even in low concentration, impacts the aquatic life by preventing the photosynthesis process and it can be considered as toxic chemicals endangering the human's health. In this study three newly synthesized Task Specific Ionic Liquids (TSILs) incorporating different types of aromatic group on imidazolium ring namely, 1-Butyl-3-Benzoimidazolium bis(trifluoromethylsulfonyl)imide BzBImNTf2; 1-Butyl-2-Phenyl-imidazolium bis(trifluoromethylsulfonyl)imide BPhImNTf2; and 1-Benzyl-3-butyl-imidazolum bis(trifluoromethylsulfonyl)imide BnBImNTf2 have been employed to remove swiftly heavy loads (up to 1,500Â ppm) of cationic Methylene Blue dye (MB) from aqueous solution without pH adjustment. The results showed that the presence of additional aromatic groups has a significant effect on the extraction efficiency of MB removal through enhancement of the ÏâÏ interactions between ILs and the aromatic structure of MB. Conductor-like Screening Model for Real Solvent (COSMO-RS) was used to analyse the IL-MB interaction in the studied systems. Finally, an original microbiological method has been designed not only to assess the toxicity of aqueous solution before and after the extraction process to reveal the industrial potential of this methodology but also to highlight the high hydrophobicity of these new TSILs. Â© 2016 Elsevier Ltd